Workplace Deviance Among Hotel Employees : An Exploratory Survey - Faridahwati Mohd. Shamsudin (Malaysian Management Journal, 2020)
This exploratory study examined workplace deviance among hotel employees in Langkawi, Malaysia. Specifically, it attempted to provide empirical answers to two main research questions: (1) what are the types of workplace deviance employees exhibit at the workplace, and (2) what work-related factors account for the exhibition of those acts. In order to address these questions, data were collected from 308 hotel employees. The findings showed that workplace deviance exists in organisations and takes on a variety of forms. The results also depicted that workplace deviance is influenced by a number of work-related factors, such as pay, supervision, co-workers, and management practices. In addition, employee deviance was also significantly related to the way they were treated by hotel guests. The implications of the study’s findings on practice and theory are discussed.